Removal and recycling of selenite anions by iron-doped cobalt-based metal organic frameworks for oxygen evolution reaction. (15th February 2023) - Ma, Shuangchen; Xu, Fang; Fan, Shuaijun; Liu, Jin; Wu, Kai; Qiu, Mingjie
Graphical abstract: Highlights: A novel Fe-doped cobalt-based metal organic frameworks was prepared by a one-step method. Co/Fe-MOF was used to uptake SeO3 2-, and the maximum adsorption capacity was 283.11 mg g −1 of Co-MOF. Under the condition of sacrificing a small amount of adsorption capacity, Co0.90 Fe0.10 -MOF can be used in the broader pH range with higher stability. U-Co/Fe were recycled utilization as an OER electrocatalyst in wastewater treatment process. Abstract: As the main form exists in selenium-containing wastewater, selenite (SeO3 2- ) is often produced by human activities and is exceedingly difficult to be removed from wastewater. In this study, five iron-doped (Fe-doped) cobalt-based metal organic frameworks (Co/Fe-MOF) with different metal ratios were prepared to remove SeO3 2- anions. The prepared Co/Fe-MOF were confirmed by characterization and their adsorption properties experiments. They have excellent SeO3 2- removal performance at pH of 3–8 with a maximum adsorption capacity of 283.11 mg g −1 of Co-MOF. After uptaking SeO3 2- by Co/Fe-MOF, the used Co/Fe-MOF (U-Co/Fe) contains CoSeO4 and Fe2 (SeO4 )3 and can be used as electrocatalytic oxygen evolution catalysts. Their oxygen/selenium vacancies can reduce the overpotential of the oxygen evolution reaction (OER). In 1.0 M KOH, U-Co0.90 Fe0.10 displayed the lowest overpotential 326 mV at 10 mA cm −2 . This study reveals the mechanism and resource upgrading process of SeO3 2- removal by Co/Fe-MOF and demonstrates that a small amount of Fe doping could improve the performance of OER.